UTAUT3 Assessment on Generation Z Muslim QRIS Users to Encourage A Cashless Society in Indonesia - Romadhon, Rizki; Sukardi, Budi (MALIA: Journal of Islamic Banking and Finance, 2024)
Technological advances have encouraged the development of digital financial services, including the use of QRIS in Indonesia. Generation Z Muslims, with strong digital skills, play an important role in the transition to a cashless society. This study aims to understand the factors that affect the interest of Generation Z Muslims in using QRIS. The methodology used was a quantitative approach with a purposive sampling technique, involving 323 respondents from Generation Z Muslims in Sesolo Raya and data analysis was carried out using Smart PLS 4.0 with the UTAUT 3 model. The results show that performance expectations, personal innovation, and habits have a significant effect on the behavioral intention of using QRIS, while the price value also has an important impact. Although several other factors did not have a significant effect, this generation proved to be key in driving the adoption of QRIS and accelerating the transition to a cashless society in Indonesia. Behavioral intentions also have a significant effect on usage behavior.